2021
DOI: 10.1002/adfm.202009376
|View full text |Cite
|
Sign up to set email alerts
|

Ultraflexible and Malleable Fe/BaTiO3 Multiferroic Heterostructures for Functional Devices

Abstract: The high demand for flexible spintronics based on multiferroic heterostructures makes growing high‐quality flexible, functional oxides urgently, in which needs to be deposited on lattice‐matched substrates. In this paper, ultraflexible and malleable iron (Fe)/BaTiO3 (BTO) multiferroic heterostructures are demonstrated, showing a perfect crystallinity and hetero‐epitaxial growth. In terms of performance, they indicate good multiferroic properties and excellent bending tunability, as well as obvious magnetoelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…Freestanding BFO films were lifted by dissolving the SAO sacrificial layer in deionized water with mechanical support from PDMS tape or silicon-coated PET and then transferred onto the desired substrates. Furthermore, Zhao et al [40] prepared freestanding Fe/BaTiO 3 (BTO) multiferroic heterostructures by using the SAO sacrificial layer. Pesquera et al [41] reported the fabrication of multiferroic LSMO/0.68Pb(Mg 1/ 3 Nb 2/3 )O 3 -0.32PbTiO 3 (PMN-PT) heterostructures by the epitaxial transfer technique using SrRuO 3 as a sacrificial layer.…”
Section: Methods Of Fabricating Flexible Multiferroic Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Freestanding BFO films were lifted by dissolving the SAO sacrificial layer in deionized water with mechanical support from PDMS tape or silicon-coated PET and then transferred onto the desired substrates. Furthermore, Zhao et al [40] prepared freestanding Fe/BaTiO 3 (BTO) multiferroic heterostructures by using the SAO sacrificial layer. Pesquera et al [41] reported the fabrication of multiferroic LSMO/0.68Pb(Mg 1/ 3 Nb 2/3 )O 3 -0.32PbTiO 3 (PMN-PT) heterostructures by the epitaxial transfer technique using SrRuO 3 as a sacrificial layer.…”
Section: Methods Of Fabricating Flexible Multiferroic Filmsmentioning
confidence: 99%
“…Furthermore, Feng et al [49] predicted that the magnetoelectrical properties strongly improved in the case of LSMO/BFO superlattice. Zhao et al [40] demonstrated the growth of multiferroic Fe/BaTiO 3 (BTO) heterostructures by using the PLD technique, followed by transfer of the Fe/BTO functional layer on PDMS substrates. The flexible Fe/BTO/PDMS heterostructures exhibited good ferroelectric and ferromagnetic behavior with a bending radius of 5 mm.…”
Section: Multiferroic Properties On Flexible Substratesmentioning
confidence: 99%
“…[ 28–31 ] In this way, we obtained the freestanding epitaxial (100)‐oriented BaTiO 3 (BTO) films remaining excellent ferroelectricity and flexibility. [ 32,33 ] However, (100)‐oriented BTO films do not possess strong E b as (111)‐oriented BTO films do. This is because the (111)‐oriented BTO exhibits a much lower electrostrictive coefficient, resulting in a reduced electric‐field‐induced strain along the direction of the electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible spintronic materials have been studied systematically for the integration of conventional magnetic sensors such as anisotropic magnetoresistive coupling effect as well as excellent flexibility. [9] Although freestanding single-crystalline ferroelectric and multiferroic membranes have exhibited extraordinary flexibility, freestanding single-crystalline multiferroic membranes with PMA remains unexplored.…”
Section: Introductionmentioning
confidence: 99%